Implementasi Kebijakan Pelimpahan Kewenangan Pelayanan Perizinan Dan Non Perizinan pada Dinas Penanaman Modal Dan PelayananTerpadu Satu Pintu Kota Langsa - Ana Zahara (Asia-Pacific Journal of Public Policy, 2022)
Langsa Mayor Regulation Number 32 of 2018 concerning Delegation of Authority for Licensing and Non-Licensing Services at the Langsa City Investment and One-Stop Integrated Service Office has not been realized effectively because problems still occur in implementing the policies that have been set. The problem is that people who want to take care of licensing and non-licensing still do not know the requirements that have been set, so licensing and non-licensing cannot be processed. This research type is descriptive qualitative, using techniques to obtain data through interviews, observation, and documentation. Data analysis techniques are taken through data collection, data reduction, data presentation, and concluding. The informants used were eight people who were determined purposively, consisting of the head of the service, employees, and the community. The results showed that the implementation of the Policy on Delegation of Authority for Licensing and Non-Licensing Services by taking a location at the City Investment and One-Stop Integrated Service Office requires coordination and cooperation with many parties. Therefore, there needs to be a communication relationship in the internal bureaucracy that runs one way and the objectives and the communication that exists between each party must run in harmony. The effort that needs to be made is to provide socialization to the community to increase their awareness of how important it is to take care of permits and complete each of the requirements that have been set